A rare presentation of hypothyroidism - Mathew, Betsy; Francis, Geetha Ann; Thomas, Kurian (International Journal of Research in Medical Sciences, 2017)
In this case report, we have brought out a very rare presentation of hypothyroidism in the form of cataplexy and this case is of significance because there have been no similar case reports of hypothyroidism presenting as cataplexy so far. The other highlight of the case is that treatment of hypothyroidism alone resulted in complete freedom from cataplexy without the need for agrypnotic drugs.